Role of mast cells in the pathogenesis of hypersensitivity pneumonitis. Issue 8 (August 1987) - Soler, P; Nioche, S; Valeyre, D; Basset, F; Benveniste, J; Burtin, C; Battesti, J P; Georges, R; Hance, A J
Abstract : To examine the possibility that mast cells have a central role in the pathogenesis of hypersensitivity pneumonitis, 20 patients with this disease were studied with the aim of seeking evidence for mast cell degranulation. The number of mast cells recovered by bronchoalveolar lavage from patients with hypersensitivity pneumonitis was more than 1, 000 times greater than those recovered from normal individuals. Furthermore, discontinuation of antigen exposure resulted in an increase in the number of mast cells observed, consistent with the possibility that antigen exposure had induced mast cell degranulation. Cessation of antigen exposure also resulted in a rapid decrease in the number of neutrophils and eosinophils recovered by lavage, followed by an increase in the number of T8+ T lymphocytes present. In each case the time course of the changes was consistent with the possibility that mast cell degranulation had been important in regulating the number of the immune and inflammatory cells present in the lung. Histamine was present in lavage fluid supernatant from patients with hypersensitivity pneumonitis. The amount of histamine present was, however, closely correlated with the number of mast cells present and not with the interval since last antigen exposure. Delay in separating cells from lavage fluid supernatant resulted in an increase in histamine content. These results suggest that the free histamine in lavage fluid resulted from the degranulation of mast cells induced by the lavage procedure as histamine released in vivo has a short half life. We suggest that hypersensitivity pneumonitis results from a "late phase reaction" initiated by antigen induced mast cell degranulation.